Tourism space and cultural tourism through the Don Vasco route in Michoacán, Mexico - Zúñiga-Bravo, Federico Gerardo (2019)
The objective of this work is to present the conformation of the tourism space in the state of Michoacán, Mexico, based on the analysis of the Don Vasco route. A touristic-cultural route whose design, planning and management seeks to promote cultural tourism through the enhancement of the existing cultural and natural heritage in two of the ten geographical regions that characterize the entity: Lacustre and Meseta Purhépecha regions. The present research is comprised of two sections: the first outlines the natural, historical and sociocultural basis that supports tourism growth in the study area; the second, by way of applying the Space Articulation Model as the main methodological resource, identifies the elements around which tourism space is built: the touristic resources and services, the spatial channels of tourist articulation, as well as the exchange flows that these originate at the national and foreign levels.